2006
DOI: 10.1159/000091634
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis-Induced Koro-Like Syndrome

Abstract: The genital-shrinking syndrome is a transient state of acute anxiety characterized by the triad of a deep-seated fear of penile shrinkage, its disappearance into the abdomen, and apprehension regarding inevitable impotence or even death. It is also known by the Malayo-Indonesian term ‘koro’. In the West, koro syndrome has been reported only in relation with various somatic, psychiatric and drug-induced disorders. The vast majority of non-psychiatric cases was related to neurological disorders or intoxication w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…24 Two examples of druginduced Koro syndrome have also been reported in a case involving cannabis and alcohol-induced hepatitis. 25,26 The example of alcoholic hepatitis induced Koro syndrome also involved a urinary tract infection which is consistent with other physical risk factors involving problems with the urogenital system. 26…”
Section: Psychiatric Risk Factors and Comorbiditiessupporting
confidence: 75%
“…24 Two examples of druginduced Koro syndrome have also been reported in a case involving cannabis and alcohol-induced hepatitis. 25,26 The example of alcoholic hepatitis induced Koro syndrome also involved a urinary tract infection which is consistent with other physical risk factors involving problems with the urogenital system. 26…”
Section: Psychiatric Risk Factors and Comorbiditiessupporting
confidence: 75%
“…2 The onset of Koro is often associated with cannabis, alcohol, amphetamine intoxication, or heroin withdrawal. 3,18,46 Even a one-time use of cannabis can induce a severely distressing mental health condition such as Koro. 47…”
Section: Literature Reviewmentioning
confidence: 99%
“…Given the evolution of its classification, both conceptual and descriptive inadequacies are found in the DSM's definition; therefore, there is a need for further debate about what constitutes an "exotic deviance". 8,46,[51][52][53][54][55][56][57][58][59] Etiologies, Formulation, and Models Koro has been described as a condition that is caused by the devil, especially in Southeast Asia. Indeed, past studies have shown that laypeople implicitly believe that Koro is a state of demonic possession.…”
Section: Classification and Diagnostic Associationsmentioning
confidence: 99%
See 1 more Smart Citation